Role of the renin–angiotensin system on abdominal aortic aneurysms. (21st October 2013) - Malekzadeh, Sonaz; Fraga‐Silva, Rodrigo A.; Trachet, Bram; Montecucco, Fabrizio; Mach, François; Stergiopulos, Nikolaos
Abstract Background Abdominal aortic aneurysm (AAA) is a complex degenerative disease, which leads to morbidity and mortality in a large portion of the elderly population. Current treatment options for AAA are quite limited as there is no proven indication for pharmacological therapy and surgery is recommended for AAA larger than 5·5 cm in luminal diameter. Thus, there is a great need to elucidate the underlying pathophysiological cellular and molecular mechanisms to develop effective therapies. In this narrative review, we will discuss recent findings concerning some potential molecular and clinical aspects of the renin–angiotensin system (RAS) in AAA pathophysiology. Materials and methods This narrative review is based on the material found on MEDLINE and PubMed up to April 2013. We looked for the terms 'angiotensin, AT1 receptor, ACE inhibitors' in combination with 'abdominal aortic aneurysm, pathophysiology, pathways'. Results Several basic research and clinical studies have recently investigated the role of the RAS in AAA. In particular, the subcutaneous infusion of Angiotensin II has been shown to induce AAA in Apo56 knockout mice. On the other hand, the pharmacological treatments targeting this system have been shown as beneficial in AAA patients. Conclusions Emerging evidence suggests that RAS may act as a molecular and therapeutic target for treating AAA. However, several issues on the role of RAS and the protective activities of angiotensin‐converting enzyme (ACE) inhibitors and Angiotensin 1 receptors blockers against AAA require further clarifications.